2004
DOI: 10.1111/j.1460-9568.2004.03537.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive tuning of corticospinal excitability during human gait: adaptation to the phase

Abstract: The aim of this study was to investigate how the cognitive tuning of corticospinal (CS) excitability adapts to the type of evoked-movement (Flexion vs. Extension) during human gait. Transcranial magnetic stimulation (TMS) was used both as a central perturbation evoking a movement and as a tool for quantifying the CS excitability of the muscles under study (RF/BF). In the first condition (Dst), the TMS occurred at mid-stance, inducing hip extension, whereas in the second condition (Dsw), the TMS occurred at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…For such immediate effects, transcranial magnetic stimulation (TMS) studies identified predominantly cortical plasticity such as increased motor cortex excitability and enlargement of motor cortical representation (Classen et al, 1998;Pascual-Leone et al, 1994, 1995. Analogous to hand function, gait and postural control are highly adaptable and underlie specific cortical control (Bonnard et al, 2002;Camus et al, 2004;Christensen et al, 2001;Schubert et al, 1999;Taube et al, 2006). Likewise, short-term motor skill training in the leg muscles induces increased motor cortex excitability, which is consistent with findings in the upper limb suggesting a similar underlying principle (Perez et al, 2004).…”
Section: Introductionsupporting
confidence: 66%
“…For such immediate effects, transcranial magnetic stimulation (TMS) studies identified predominantly cortical plasticity such as increased motor cortex excitability and enlargement of motor cortical representation (Classen et al, 1998;Pascual-Leone et al, 1994, 1995. Analogous to hand function, gait and postural control are highly adaptable and underlie specific cortical control (Bonnard et al, 2002;Camus et al, 2004;Christensen et al, 2001;Schubert et al, 1999;Taube et al, 2006). Likewise, short-term motor skill training in the leg muscles induces increased motor cortex excitability, which is consistent with findings in the upper limb suggesting a similar underlying principle (Perez et al, 2004).…”
Section: Introductionsupporting
confidence: 66%
“…Indeed, it has been shown that corticospinal excitability is tuned according to the level of cognitive engagement during gait [67][68]. In addition, the improvement in locomotor control in people with m-iSCI is associated with increased corticospinal drive to leg muscles [69][70].…”
Section: Active Engagement In Trainingmentioning
confidence: 99%
“…As compared to ankle muscles, which are involved in foot placement during locomotion for which the corticospinal control is crucial [1], Quadriceps may be involved in the postural control, which, in the light of the present results, could be assigned to sub-cortical structures. However, the present results were obtained during treadmill locomotion, without perturbation, and we assume that the cortical contribution to Quadriceps activity might be reinforced during volitional step control [5,25,26].…”
Section: Discussionmentioning
confidence: 58%